STUDI LITERATUR: IMPLEMENTASI DAN DAMPAK PENGGUNAAN ANALISIS ANGGARAN TERHADAP PENGENDALIAN KEUANGAN DI INDUSTRI MANUFAKTUR - Ravel Anwar; Zakiyatul Amaliyah; Raisa Dea Fitrasari; Rachman Hadi (Bajang Institute, 2024)
Managing finances within the manufacturing industry is crucial to a company's success. Without adequate control, companies may face the risk of inflated production costs and financial losses. Budget analysis, through the periodic creation, monitoring, and evaluation of budgets, is an essential tool for financial planning and control. This research reviews the literature on the implementation and impact of budget analysis in financial control within the manufacturing industry. The scope encompasses the implementation process, the use of technology, constraints, challenges, and their impact on the effectiveness of financial control, operational efficiency, accountability, transparency, and financial performance. The methodology employed is a literature review from sources such as Google Scholar, JSTOR, ScienceDirect, and IEEE Xplore, using keywords such as 'budget analysis' and 'financial control.' The data collection procedure involves searching, evaluating abstracts, selecting articles, and conducting an in-depth analysis. The findings indicate that budget analysis can enhance operational efficiency, reduce costs, and improve accountability and transparency, collectively enhancing the company's financial performance. The challenges encountered include resistance from organizational culture and the need for technological adaptation. The recommendations include investing in staff training, adopting appropriate technology, and enhancing transparency